Factors Influencing Health Facility Births: Insights from the 2017 Pakistan Demographic Health Survey - Shahzad, Amir; Ali, Nazakat; Ahmad, Hafiz Bilal (Journal of Development and Social Sciences, 2024)
Infant mortality in Pakistan was alarmingly high until the early 1990s, at 86 deaths per 1,000 live births. Despite a 24-point decline over the past three decades, reducing the rate to 62 per 1,000, Pakistan remains among countries with the highest infant mortality rates. This study evaluated the extent, causes, and associated risk factors of infant mortality in Pakistan. Using Univariate and cross-tabulation analyses, data were weighted by survey year. A two-stage multi-variable logistic regression model analyzed the risk factor of childbirth in health facilities. Results included odds ratios (OR) and Chi-square tests for categorical differences. Interviews with 167,151 women revealed 84,352 (50.46%) gave birth in health facilities: 22,089 in 1991, 8,166 in 2007, 11,751 in 2013, and 41,372 in 2017. Health facility births rose from 13.6% in 1991 to 64% in 2017. Urban residence, age 30+, secondary education, and government employment were significant factors in health facility usage.